Plant–soil feedbacks and the introduction of Castanea (chestnut) hybrids to eastern North American forests. Issue 3 (8th January 2021) - Coughlin, Aeran M.; Shefferson, Richard P.; Clark, Stacy L.; Wurzburger, Nina
Abstract : The reintroduction of disease‐resistant hybrids is a commonly proposed solution to the introduction of pathogens and pests that weaken or eliminate native plant species. Plant interactions with soil biota result in plant–soil feedbacks (PSFs), which have consequences for individual plant growth and survival as well as broader community‐level processes, such as species diversity and coexistence. Because of their importance, species reintroduction should consider these interactions, yet little work has integrated this perspective. Here, we investigate the effects of hybrid Castanea (chestnut) reintroduction on PSFs and how these mechanisms may influence the recruitment of other species in contemporary forests. We also examine how blight‐resistant Castanea hybrids perform in the soil conditions of contemporary forests and we compare their belowground interactions with those of Castanea dentata . We conducted a reciprocal greenhouse experiment testing the effect of species‐specific soil inoculum on the growth and survival of C. dentata, Castanea hybrids, and other forest dominants. Our results suggest that C. dentata and hybrids had similar belowground interactions and were regulated by negative PSFs, meaning soil microbial communities reduced conspecific growth and survival. These negative PSFs may involve the presence of the non‐native pathogen Phytophthera cinnamomi . Soil inoculum of C. dentata and Castanea hybrids had similar effects on heterospecific growth, suggesting Castanea restoration will have neutral effects on natural regeneration in restoration plantings. We conclude that Castanea hybrids may fill a similar belowground niche to their parent species, and that site selection, screening for soil pathogens, and site planting density will be important to restoration.